Through Bibliometric Analysis: Digital Maturity as an Emerging Topic in Entrepreneurial Economics - Loso Judijanto; Ardyan Firdausi Mustoffa; Lainatusshifa Kemal; Machfud Machfud; Sulistio Ningsih (The Es Economics and Entrepreneurship, 2026)
This study examines the development of digital maturity as an emerging topic in entrepreneurial economics through a bibliometric analysis of publications indexed in the Scopus. The objective is to map the intellectual structure, research trends, and thematic evolution of the field. A dataset of peer-reviewed articles published between 2000 and 2025 was analyzed using bibliometric techniques, including co-authorship analysis, citation analysis, keyword co-occurrence, and visualization mapping with VOSviewer. The results show a significant growth in publications after 2018, indicating increasing academic attention to digital maturity in response to global digital transformation trends. Network visualization reveals that the field is centered around economic concepts, particularly economics, industrial economics, and digital economy, while also integrating themes related to technology, management, and sustainability. Overlay visualization highlights a shift from technology-focused research toward strategic and sustainability-oriented topics, such as circular economy and sustainable development. Meanwhile, density analysis confirms a core-periphery structure, where economic themes dominate, and emerging topics such as digital maturity models, big data, and emerging economies present opportunities for future research. The study concludes that digital maturity is a multidimensional and evolving construct that bridges technological capabilities with economic and organizational performance. It contributes to the literature by providing a comprehensive mapping of the field and identifying key research gaps, particularly the need for integrated theoretical frameworks and broader empirical studies in developing economies. The findings offer valuable insights for researchers, practitioners, and policymakers in understanding the strategic role of digital maturity in fostering innovation and sustainable entrepreneurial growth.